DETERMINANTS OF INTEREST IN SAVING FOR STUDENTS IN ISLAMIC BANKING - murniati, wahyuning; Juliasari, Deni; Hanifah, Nani (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
Saving money is the way to regulate our finance effectively. Bank is one of the media that is considered quite effective for this activity. The development of Islamic economic make sharia banking practices increase in an innovative way. Various sharia bank products have become a choice for saving activity. The same thing happen for student. Although the interest to save is still lacking, but the use of sharia bank products is quite beneficial for their future. The purpose of this study is to analyze the factors that influence student interest in saving on Islamic banking. Multiple linear regression is an analysis technique with hypothesis testing to support its conclusions. With a coefficient of determination of 61.2%, the results of the analysis show the level of student education of the sharia economy has a significant effect compared to other variables on students' interest in saving. But simultaneously, all independent variables influence the interest in saving students in Islamic banking. This shows that education is very important for students, therefore STIE Widya Gama Lumajang should indeed provide quality teaching to students, especially in the field of Islamic economics